Implementasi Prinsip Pacta Sunt Servanda dalam Perjanjian Internasional Menurut Konvensi Wina 1969 - Qyan Hari Simartla Gudangga; Thalitha Olga Zhafira; Diana Permata Hati (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
International treaties are important legal instruments in regulating relations and cooperation among states, therefore their implementation must be based on clear and binding legal principles. One of the fundamental principles in the law of treaties is pacta sunt servanda, which affirms that every treaty in force is binding upon the parties and must be performed in good faith as stipulated in Article 26 of the 1969 Vienna Convention. This study uses a normative legal research method with statutory and conceptual approaches, conducted through library research on the 1969 Vienna Convention, books, journals, and other relevant legal literature. The discussion focuses on the regulation of the pacta sunt servanda principle under the 1969 Vienna Convention and its implementation in the practice of international treaties. The study finds that pacta sunt servanda constitutes the main basis that gives binding force to international treaties and obliges states to perform treaty provisions in good faith, while also preventing states from invoking national law as a justification for failing to carry out treaty obligations as emphasized in Article 27 of the 1969 Vienna Convention.